ASEAN+3 bond market guide 2016 : Thailand (ASEAN+3 bond market guide 2016 : Thailand, 2016)
Cover – Title – Copyright – Contents – Tables, Figures, and Box – Tables – 2.1 Examples of Securities Market Legislation in Each Legislative Tier – 2.2 Identification of Securities and Exchange Commission, Thailand Regulations-First Abbreviation – 2.3 Identification of Securities and Exchange Commission, Thailand Regulations-Second Abbreviation – 2.4 Regulatory Processes by Corporate Issuer Type – 3.1 Outstanding Commercial Paper across Categories – 3.2 Segmentation of the Market-Outstanding Value by Type of Bond or Note – 6.1 Thai Bond Market Association Registration Fees6.2 Duties and Taxes on Fixed-Income Securities – A1 Group of Thirty Recommendations-Compliance for Thailand – Figures – 1.1 Local Currency Bonds Outstanding in Thailand – 2.1 Roles of the Public Debt Restructuring and Domestic Bond Market Development Fund in Supporting Thai Bond Market Development – 2.2 Regulatory Process Map-Overview – 2.3 Regulatory Process for Issuance by Nonresident (Foreign) Issuer – 2.4 Regulatory Process for Issuance by Resident Financial Institution Issuer (Capital Raising Only) – 2.5 Regulatory Process for Foreign Currency Issuance4.1 Thailand Bond Exchange Market Overview – 4.2 Daily Market Highlight – 4.3 Thai Bond Market Association Government Bond Yield Curve – 4.4 Thai Bond Market Association Index – 4.5 Tenure of Bilateral Repo – 4.6 Outstanding Value of Private Repo – 4.7 Thailand Futures Exchange Interest Rate Future Page – 10.1 Securities and Exchange Commission News Release on AMBIF Pilot Issue – Box – Securities Issuance Framework in Thailand – Foreword – Acknowledgments – Abbreviations – I. Overview – A. Introduction – B. Historical Development of the Thai Bond MarketII. Legal and Regulatory Framework – A. Legal Tradition – B. English Translation – C. Legislative Structure – D. Thai Bond Market Regulatory Structure – E. Securities Issuance Framework – F. Securities Issuance Regulatory Processes – G. Continuous Disclosure Requirements in the Thai Bond Market – H. Self-Regulatory Organizations in the Thai Bond Market – I. Thai Bond Market Association Rules Related to Trading, Reporting, and Registration – J. Thailand Bond Exchange Rules Related to Bond Listing, Disclosure, and Trading – K. Market Entry Requirements (Nonresidents)L. Market Exit Requirements (Nonresidents) – M. Regulations and Limitations (Nonresidents) – N. Regulations on Credit Rating Agencies – III. Characteristics of the Thai Bond Market – A. Definition of Securities – B. Types of Bonds and Notes – C. Money Market Instruments – D. Segmentation of the Market – E. Methods of Issuing Bonds (Primary Market) – F. Governing Law and Jurisdiction (Bond and Note Issuance) – G. Language of Documentation and Disclosure Items – H. Registration of Debt Securities – I. Listing of Debt Securities – J. Methods of Trading Bonds and Notes (Secondary Market)K. Bond and Note Pricing